Contextual Approach-Based E-Module Assessment to Improve Students' Critical Thinking Ability and Skills - Yuliastrin, Adisti; Vebrianto, Rian; Radeswandri, Radeswandri; Maisyaroh, Fahkroh Zulfi (Edunesia : Jurnal Ilmiah Pendidikan, 2023)
The research objective of this article is to provide an overview of assessment in the form of improving students' critical thinking abilities and skills through a quality science learning contextual approach. This article discusses several formulations of the problem: E-Modules based on a practical contextual approach to improve students' critical thinking skills, E-Modules based on an efficient contextual approach to improving students' critical thinking skills, and the effect of using E-Modules in the Middle School Science learning process. The form of the research used was the RnD model instrument development research (Allesi and Trollip) which involved 35 respondents. This research involved 35 respondents from several students, teachers, and lecturers. Data is collected in Google form. After that, the data was processed and analyzed using SPSS 0.16. The study results show that the E-Module media is effective and efficient for use in the teaching and learning process and influences the learning process for junior high school students. This study shows that e-module teaching media can be preserved and used in teaching and learning. This article shows that e-module media can be used in the teaching-learning process. It is hoped that the existence of teaching media assessment instruments in the form of e-modules that are memorable in innovative and efficient teaching and learning processes.